2003
DOI: 10.1023/b:bigi.0000007777.87407.1b
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA Sequence-Based Population Genetic Structure of the Firefly, Pyrocoelia rufa (Coleoptera: Lampyridae)

Abstract: The genetic divergence, population genetic structure, and possible speciation of the Korean firefly, Pyrocoelia rufa, were investigated on the midsouthern Korean mainland, coastal islets, a remote offshore island, Jedu-do, and Tsushima Island in Japan. Analysis of DNA sequences from the mitochondrial COI protein-coding gene revealed 20 mtDNA-sequence-based haplotypes with a maximum divergence of 5.5%. Phylogenetic analyses using PAUP, PHYLIP, and networks subdivided the P. rufa into two clades (termed clade A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…Recently, Bae et al (2004) determined the mtDNA genome of a lampyrid species, Pyrocoelia rufa, from Korea. The partial sequences of mtDNA, including COI (Kim et al, 2000;Lee et al, 2003), COII (Suzuki et al, , 2004, and lrRNA (Suzuki, 1997;Kim et al, 2000;Li et al, 2006), have also been determined and used to investigate the evolutionary and biogeographic relationships of this family in East Asia. For example, phylogenetic analysis has shown that the firefly Luciola cruciata dates back ∼ 0.5 million years in the Japanese islands and that there are genetic differences between the eastern and western Japanese forms .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Bae et al (2004) determined the mtDNA genome of a lampyrid species, Pyrocoelia rufa, from Korea. The partial sequences of mtDNA, including COI (Kim et al, 2000;Lee et al, 2003), COII (Suzuki et al, , 2004, and lrRNA (Suzuki, 1997;Kim et al, 2000;Li et al, 2006), have also been determined and used to investigate the evolutionary and biogeographic relationships of this family in East Asia. For example, phylogenetic analysis has shown that the firefly Luciola cruciata dates back ∼ 0.5 million years in the Japanese islands and that there are genetic differences between the eastern and western Japanese forms .…”
Section: Introductionmentioning
confidence: 99%
“…This estimate for COI is quite high considering other relevant studies, which utilized homologous COI gene. For example, the estimate was 0.2% for the domestic silkworm (Kim et al, 2000), 0.2% and 1.2% for two species of mushroom flies (Lee et al, 2003), and 11% for the oriental mole cricket (Kim et al, 2007a). The two firefly species and the mole cricket have been reported to have a taxonomic implication Lee et al, 2003;Kim et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Mitochondrial DNA-based population genetic structures of insect species in the Korean Peninsula have been determined for several insect species belonging to Coleoptera, Diptera, Lepidoptera, and Hymenoptera Kim et al 2001Kim et al , 2003aLee et al 2003;Yoon et al 2003). In those studies, the haplotypes of some of the species could be subdivided into two or more distinct geographic groups, thereby reflecting the genetic isolation among regions.…”
Section: Phylogeographymentioning
confidence: 99%